2005
DOI: 10.1002/ffj.1427
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the volatile oils of Phlomis lanceolata Boiss. & Hohen., Phlomis anisodonta Boiss. and Phlomis bruguieri Desf. from Iran

Abstract: The composition of hydrodistilled essential oils of three species of Phlomis (Lamiaceae), P. lanceolata, P. anisodonta and P. bruguieri, were investigated by GC and GC-MS, and 31, 28 and 21 compounds, representing 94.1%, 96.0% and 96.8%, respectively, of the total oils, were identified. In all three samples, sesquiterpenes were the main components. In P. lanceolata oil the main components were germacrene D (47.0%), (E)-β β β β β-farnesene (10.5%), α α α α α-pinene (8.7%), germacrene B (8.0%), bicyclogermacrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…c Essence or "jing": means something specific of Korean traditional medicine. Sarkhail et al (2005) Phlomis bruguieri Germacrene D (60.5%), ␥-elemene (16.5%), germacrene B (7.1%), bicyclogermacrene (4.1%). Phlomis olivieri (DAP/H) Germacrene D (26.4%) and bicyclogermacrene (12.7%).…”
Section: The Part Of Phlomis Usedmentioning
confidence: 99%
“…c Essence or "jing": means something specific of Korean traditional medicine. Sarkhail et al (2005) Phlomis bruguieri Germacrene D (60.5%), ␥-elemene (16.5%), germacrene B (7.1%), bicyclogermacrene (4.1%). Phlomis olivieri (DAP/H) Germacrene D (26.4%) and bicyclogermacrene (12.7%).…”
Section: The Part Of Phlomis Usedmentioning
confidence: 99%
“…While this genus is known to produce a variety of compounds, including terpenoids, iridoids, phenylethanoids, phenylpropanoids and flavonoids [2], thorough phytochemical investigation on P. lanceolata has not been carried out before. However, Sarkhail et al [3] reported the composition of the essential oils of this plant, and antiinflammatory and analgesic properties of P. lanceolata have also been documented [2]. As a part of our ongoing phytochemical and bioactivity studies on plants from Iranian flora [4][5][6][7][8][9][10][11][12], we now report on the isolation and structure elucidation of three phenylethanoid glycosides (1)(2)(3) and also on their antibacterial potentials against multiple-drug-resistant (MDR) strains of Staphylococcus aureus (Scheme 1).…”
Section: Introductionmentioning
confidence: 97%
“…(family: Lamiaceae) is one of the 17 endemic Iranian species of the genus Phlomis [1,2]. A number of Phlomis species have been used in traditional medicine as a stimulant and tonic, and to treat pains, respiratory tract infections, diabetes and wounds [2,3]. While this genus is known to produce a variety of compounds, including terpenoids, iridoids, phenylethanoids, phenylpropanoids and flavonoids [2], thorough phytochemical investigation on P. lanceolata has not been carried out before.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the genus Phlomis is known to produce a variety of compounds including, terpenoids, iridoids, phenylethanoids, phenylpropanoids and flavonoids [2], no phytochemical investigation on P. caucasica has ever been carried out before. As a part of our ongoing phytochemical and bioactivity studies on plants from Iranian flora [4][5][6][7][8][9][10][11][12][13][14][15][16], we report on the isolation and identification of seven antioxidant phenolic compounds (1)(2)(3)(4)(5), and two phenylethanoid glycosides (6-7) from the aerial parts of P. caucasica and also on their free-radical-scavenging properties in the 2,2-diphenyl-1-picryl hydrazyl (DPPH) assay.…”
mentioning
confidence: 99%
“…This plant grows abundantly in the Yam area located in east Azerbaijan province of Iran. A number of Phlomis species have been used in Iranian traditional medicine as a stimulant and tonic and to treat pains, respiratory tract infections, diabetes and wounds [2,3]. P. caucasica has been used in the treatment of throat infections.…”
mentioning
confidence: 99%